Tracking donor RBC survival in premature infants: agreement of multiple populations of biotin-labeled RBCs with Kidd antigen mismatched RBCs - Widness, John A. (2013)
BACKGROUND: Anemia, a common condition among critically ill premature infants, is affected by red blood cell (RBC) survival (RCS). We hypothesized that transfused allogeneic Kidd antigen mismatched RBCs would demonstrate the same concurrent RCS tracking as RBCs multi-labeled at separate, discrete low densities with biotin (BioRBCs). METHODS: Allogeneic RBCs from adult donors were labeled at four biotin densities, mixed, and transfused into 17 anemic premature infants. Nine of the donors and neonates were Kidd antigen mismatched. Serial post-transfusion blood samples were assayed for up to eight weeks by flow cytometry to track the survival of the proportions of Kidd antigen mismatched and biotinylated RBCs. RESULTS: Using linear mixed modeling to compare results, RCS of the three lowest BioRBC densities was similar to RCS by Kidd antigen mismatch and to one another. RCS of RBCs labeled at the highest BioRBC density was shortened. CONCLUSIONS: RCS of different populations of RBCs can be tracked concurrently and reliably using the three lowest BioRBC densities. Although comparable RCS results can be achieved using Kidd antigen mismatches, BioRBCs are preferred for investigating neonatal anemias because biotin labeling of both allogeneic and autologous RBCs is possible.